Ethnic and Cultural Considerations in Male Rejuvenation - Moritz, Ethan; Asaria, Jamil (Facial Plastic Surgery)
Aims and Backgrounds A patient’s ethnicity and culture need to be considered prior to male facial rejuvenation. Here, we describe the most important factors across ethnicities that affect the analysis, treatment and postoperative considerations of commonly performed procedures. Anatomy There are some traits commonly associated with certain ethnicities that differ from each other. These span skeletal structure, skin characteristics, predisposition to poor scarring, periorbital and nasal anatomy and hair qualities. Techniques As they pertain to the described differences in traits, certain variations exist within procedures to accommodate non-Caucasian patients. This is to make results more natural, fitting to a patient’s ethnicity and goals and to account for differences in postoperative healing. Conclusions and Clinical Relevance An integral part of every patient encounter is to listen to the patient’s perspective and goals prior to developing a treatment plan. Their facial analysis should subsequently be performed in the context of their ethnicity. The management of non-Caucasian facial rejuvenation patients should not be taught as a variation of the norm but rather as unique considerations to modify known surgical techniques for each individual ethnicity and culture. Training needs to emphasize and popularize these differences.